A Century of East African Integration - Amuhaya, Claire A. author. (orcid)0000-0003-4063-6049 Link aut Link
XVII, 263 p. 7 illus., 3 illus. in color.
Keywords: “This book is a magnum opus for everyone interested in regional integration. It is the only text that comprehensively traces and puts into proper conceptual, theoretical corpus and historical trajectory the evolution of integration of the East African Region.” – Korwa Gombe Adar, Professor of International Studies, University of Botswana, Gaborone, Botswana. “A timely reference for researchers and policy makers” – Kasaija Phillip Apuuli, Associate Professor, Makerere University, Kampala, Uganda. “This book offers a rich, fresh, century historical in-depth analysis of Regional Integration in East Africa filling a gap on African Integration literature.” – Alexander BALEZIN, Professor, Dr. of Science, Principal researcher - Institute of World History, Russian Academy of Sciences. This book presents a comprehensive historical analysis of regional integration in the East Africa sub–region in the last century. Itpays particular attention to the cyclicality of integration dynamics, as well as the analysis of the interconnection and competition between different regional organizations in East Africa. In this context, the specificity of the so-called overlapping membership of African states in regional organizations with similar roles but conflicting treaties and mandates is explored. This situation to a certain extent affects trade relations of states in the region with external actors specifically with the EU that the book comprehensively analyses. This book therefore offers a deeper understanding of the processes of regional integration in East Africa, previously overlooked reflecting the general integration dynamics on the African continent. Dr. Claire A. Amuhaya is a Researcher and Assistant at the Department of Theory and History of International Relations at RUDN University, Moscow. Her main Research interest is Africa and she has published several works in leading journals. Professor Denis A. Degterev is the HoD of Theory and History of International Relations at RUDN University, Moscow, he also teaches at MGIMO-University, MFA of Russia and Saint Petersburg State University. He has written extensively on Global South publishing over 200 papers in leading journals. He specializes on development cooperation and in 2002-2005 he worked in West Africa.